PENGARUH IMPLEMENTASI KEBIJAKAN ETIKA JABATAN TERHADAP KINERJA APARATUR BIROKRASI ( Suatu Studi Di Sekretariat Daerah Propinsi Sulawesi Utara ) - KAUNANG, REZHA; SONDAKH, TELLY; OGOTAN, MARTHA (Sam Ratulangi University, 2014)
ABSTRAK : PP.42 of 2004 mandated that in the execution of official duties and everyday life and everycivil servant is obliged to be guided by the ethical position that applies to all civil servants. However, inreality the values or ethical norms contained in the policies of the ethics office has not been fullyimplemented in earnest by the bureaucratic apparatus (PNS), so that may have an impact on performance.The purpose of this study was to determine the effect of the implementation of ethics policies on theperformance of bureaucratic positions in North Sulawesi Provincial Secretariat.The method used in this study is a quantitative method. Source of data / research respondentswere as many as 50 employees were taken with a random sampling technique from 460 employees inNorth Sulawesi Provincial Secretariat. Data collection using questionnaire and assisted with interviewtechniques. The analysis technique used is the percentage analysis, linear regression analysis and productmoment correlation.The results showed: (1) variable regression coefficient ethical positions on policy implementationlevel and the performance of the apparatus is very significant posifive (2) the correlation coefficient andthe coefficient of determination of office ethics policy implementation variables on the performance of theapparatus is high / strong and highly significant.Based on the results of that study concluded that the implementation of the ethical policy positions hadfunctional relationships and positive influence on the category of high and very significant to theperformance of the apparatus in North Sulawesi Provincial Secretariat. This shows that theimplementation of civil service ethics policy positions (PP.42 2004) has been able to provide a positiveimpact for increased performance bureaucratic apparatus.Based on these conclusions suggested: (1) understanding, appreciation and practice of the ethicalprinciples set out in the civil service ethics policy positions (PP. 42 2004) needs to be an increase in thebureaucratic apparatus. (2) required the commitment of the elite bureaucracy to implement policypositions with good ethics and correct; (3) a continuous basis an assessment of the level of implementationof the ethical policy positions through a monitoring mechanism, and then evaluated and attempted repair.Keywords: ethics policy positions, performance of the apparatus.